Multi‐Level Product Platform Strategy for a Multi‐Level Corporation. (28th October 2015) - Bergsjö, Dag; Levandowski, Christoffer; Stig, Daniel Corin
Abstract: Reuse strategies based on product platform thinking can provide important advantages over single‐product development, especially for achieving economy‐of‐scale and cost‐efficient product variety. This paper presents the case of a multi‐national corporation that has many opportunities for identifying commonalities across and within its subsidiaries from which product platforms can be defined. The study focuses on the opportunities of one of these subsidiaries to transfer to platform‐based development for some of their components. A framework is presented that defines different levels in the organization where product platforms can be used, as well as different types of reuse strategies that may be adequate for the studied components. These levels are: (A) within each subsidiary, (B) between subsidiaries, and (C) common throughout the umbrella corporation. The types of reuse are categorized as (1) local component sharing, (2) arms‐length buy‐in of components within the corporation, and (3) platform‐based development. It is argued that a platform strategy for the corporation can include various combinations of reuse types and organizational levels, depending on where reuse potential is identified. The main considerations for making this effective is where ownership lies for the shared assets and how to balance multiple stakeholder requirements from different applications, e.g. during engineering change requests.